Uqubat Ta’zir for Child Offenders Convicted of Rape Under Aceh’s Jinayat Law: Balancing Child Protection and Victim Justice - Khairani Karen Azara Siregar; Muhammad Yusuf; Azwarfajri Azwarfajri (Lembaga Aneuk Muda Peduli Umat, Bekerjasama dengan LaKaspia, 2026)
The imposition of uqubat ta’zir (a discretionary punishment under Aceh’s Islamic criminal law) on a child offender convicted of rape requires courts to reconcile child-specific protection and rehabilitation with recognition of the harm experienced by a child victim. This article examines Banda Aceh Sharia Court Decision No. 1/JN.Anak/2023/MS.Bna. It asks what legal and nonlegal considerations supported the punishment and to what extent the court’s reasoning balanced protection of the child offenders with justice for the child victim. The study employed doctrinal legal research using statutory and case approaches. Its primary materials included the decision, Aceh Qanun No. 6 of 2014—a regional regulation governing jinayat (Islamic criminal law) in Aceh—and Indonesia’s juvenile justice, child-protection, and victim-recovery legislation. The court imposed 24 months of pembinaan (structured guidance and development) in a Juvenile Special Development Institution (Lembaga Pembinaan Khusus Anak, LPKA), compared with the prosecutor’s request for 48 months. The disposition remained below the statutory ceiling and reflected the offenders’ ages, remorse, absence of a previous uqubat, and prospects for rehabilitation. The court also recognized the victim’s physical and psychological harm through medical and psychological evidence. However, its reasoning did not adequately explain how the mitigating and aggravating considerations produced the specific 24-month duration or how the victim’s documented harm related to restitution and recovery. The decision therefore had an identifiable legal basis but achieved an incomplete balance between child-offender protection and victim justice at the level of judicial reasoning.